2006
DOI: 10.1016/j.socscimed.2005.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol outlets, gonorrhea, and the Los Angeles civil unrest: A longitudinal analysis

Abstract: This study tests the effect of neighborhood changes on gonorrhea rates. Prior studies that indicate gonorrhea rates are associated with alcohol outlet density and neighborhood deterioration have been cross-sectional and cannot establish causality. After the 1992 Civil Unrest in Los Angeles, 270 alcohol outlets surrendered their licenses due to arson and vandalism thus providing a natural experiment. We geocoded all reported gonorrhea cases from 1988 to 1996 in LA County, all annually licensed alcohol outlets, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 26 publications
(25 reference statements)
3
72
0
Order By: Relevance
“…However, our results are in agreement with prior related research. Studies looking at density of drinking establishments in U.S. populations have also found a significant relationship between density of drinking establishment and risk of STDs and drinking related problems [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our results are in agreement with prior related research. Studies looking at density of drinking establishments in U.S. populations have also found a significant relationship between density of drinking establishment and risk of STDs and drinking related problems [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The bottle store is a formal, registered To our knowledge, the association of density of drinking establishments with HIV prevalence has not been evaluated, particularly in the setting of a migrant town where high rates of alcohol consumption are observed. Prior research has evaluated density of drinking establishments and STI prevalence and drinking-related problems [5,6]. Cohen and colleagues [5] examined the relation between drinking establishment density and gonorrhea rates and found a significant correlation between the two (r=0.956, pvalue <0.01).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Alcohol outlet density has also been associated with a variety of social problems including violent assault, [8][9][10][11][12] alcohol-related motor vehicle accidents and fatalities, 12,13 and sexually transmitted disease rates. 14,15 Yet, other studies have found that drug-related crime is a stronger predictor of violence than alcohol outlets. 16,17 A separate consideration is that alcohol outlets are not randomly distributed in communities.…”
Section: Introductionmentioning
confidence: 99%
“…In Los Angeles, many of the 270 alcohol outlets that surrendered their licenses did not reopen (Cohen et al, 2006), and hundreds of billboards were eliminated in some cities (Herd, 2011). In Los Angeles, one of the organizers now serves as a district Congresswoman.…”
mentioning
confidence: 99%